Directions of ICT use in Ukrainian educational institutions in the educational process with children with special educational needs: A literature review - O. Kasyanenko (Mukachevo State University, 2023)
The organisation of the educational process with children with special educational needs requires the implementation of special approaches to their education. Therefore, it is important to consider the relevant foreign experience, explain the features of distance learning using information and communication technologies and develop recommendations for the use of such technologies in the educational process with children with special needs. The purpose of this study was to investigate the specific features of using information and communication technologies in preschool education institutions in teaching children with special educational needs and to cover the areas of their implementation. The methodological framework of this study included an interdisciplinary approach to the analysis of a scientific problem in combination with theoretical and empirical methods, among which the priority was given to induction, deduction, analysis, synthesis, generalisation, study of scientific literature and pedagogical observation. It was found that information and communication technologies are a set of methods, educational and methodological materials, technical means of teaching and software. It was found that they increase the effectiveness of the educational process and help to unite its participants. The study proved that the use of information and communication technologies involves the application of three approaches: technocentric, holistic, and combined. It was found that the combined approach creates a subject-object model of teaching children with special needs and demonstrates the greatest effectiveness. The study presented several classifications of information and communication technologies. The classification of information and communication technologies was presented. It was found that they are divided into main and auxiliary; standard and auxiliary; virtual. The advantages of using information and communication technologies in the educational process with children with special educational needs were considered in detail, which confirmed the need for their use in preschool education institutions in the context of distance learning. The practical significance of this study is that its results, specifically recommendations for the introduction of special approaches to the education and upbringing of preschool children with special educational needs, can be used in organising an effective educational process for such children.